URGENSI SINKRONISASI PERATURAN PELAYARAN SEBAGAI ANGKUTAN MULTI MODA UNTUK MENURUNKAN BIAYA LOGISTIK - Tentaminarto Tri Februartono; Elfrida Ratnawati Gultom (LPPM Universitas Ekasakti Padang, 2023)
The purpose of writing this paper is to describe and analyze the need for synchronization of shipping regulations as a multimodal company in relation to the economics of high logistics costs and shipping regulations that must be synchronized in order to achieve logistics cost efficiency. The main problem in this paper is the need to synchronize shipping regulations so that shipping can carry out multi-modal service transportation without having to create or change a new business form into a Multi-Mode Transport Business Entity (BUAM). Indonesia is an archipelagic country where sea transportation is important in logistics transportation, Shipping Companies as sea transportation will play a role in reducing logistics costs if they can carry out multimodal transport contracts. The methodology used in writing this paper uses normative legal research supported by secondary data, which consists of primary legal materials, namely Law Number 17 of 2008 concerning Shipping, Government Regulations, Ministerial Regulations related to issues, Secondary legal materials consist of books, journals, magazines. publications, opinions of experts and professionals in the field of law and logistics, information from the internet related to the problem, as well as tertiary legal materials in the form of dictionaries.